Application of Educational Philosophy in School Practice: A Systematic Literature Review - Mike Atnelie; Sulastri Sulastri; Tanti Permata Sari; Tri Emelia Rostari; Tri Muryanti (Journal of Social Work and Science Education, 2026)
This study aims to comprehensively examine how the application of educational philosophy manifests itself in modern school practice. Although the theoretical importance of educational philosophy has been widely discussed, a gap remains between the conceptual realm and its practical implementation in the educational field. To address this issue, this study employed the Systematic Literature Review (SLR) method guided by the PRISMA protocol. Data were collected through a systematic search of databases such as Scopus, ERIC, and Google Scholar. The inclusion criteria were articles published between 2020 and 2025 that discussed the application of educational philosophy, particularly Constructivism, Progressivism, Humanism, and Existentialism, in the context of elementary and secondary school practice. The PRISMA process included identification, screening, eligibility, and inclusion of articles to ensure transparency and validity of the study results. The review revealed that the application of educational philosophy in schools remains partial and dependent on the policy context, teacher readiness, and institutional culture. However, there is a positive trend toward a more reflective, participatory, and learner-centered approach. This research emphasizes the importance of integrating educational philosophy into pedagogical practices and policy recommendations so that philosophical values ​​do not stop at the ideal level, but are realized in real classroom actions.